Mathematical Model of a Frequency Converter of Temperature - Osadchuk, V.S.; Osadchuk, A.V. (Elektronika ir Elektrotechnika, 2000)
The researches of a frequency converter of temperature are represented on the basis of two bipolar transistors. It is shown, that such integrated circuit has a negative resistance, that has allowed to implement the generator of electrical oscillations. As a temperature sensitive element the thermistors were utillized. The calculation of the function of conversion and sensitivity is carried out. Matching theoretical and experimental results is given.